Crisis management - Нurzhii Natalia; Kulachek, Natalia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The article explores the concept and principles of crisis management. Priority problems of improving the crisis management system are determined. The specifics of enterprise management in a crisis is the need to make management decisions with a high degree of risk and limited funding. For timely warning and overcoming crises, it is imperative to apply in a complex the methods of economic analysis, forecasting, to develop special anti-crisis plans and programs. Design/methodology/approach. The basic principles of the research are historical, systematic and comparative methods, institutional and structural-functional approaches have been used. Findings. The causes of crises in the organization may be different. It is important to recognize the symptoms of crisis development and the factors that caused it in order to use crisis management programs in time. The procedure for a comprehensive analysis of all established parameters and indicators that will determine the overall situation of the enterprise in the external environment. Originality/value. Every crisis brings new business opportunities, as a result of which it either changes or disappears. In order to constantly develop, it is necessary to effectively use crisis management - it is effective not only in the midst of a crisis. Anti-crisis management at the present time is understood as such management, which is aimed not only at taking the company out of the crisis, including from a state of bankruptcy, but also at preventing deep crisis phenomena and ensuring successful development.